Positive Emotions, Autonomy Support and Academic Performance of University Students: The Mediating Role of Academic Engagement and Self-Efficacy [Emociones Positivas, Apoyo a la Autonomía y Rendimiento de Estudiantes Universitarios: El Papel Mediador del Compromiso Académico y la Autoeficacia] - Oriol-Granado, X (Escuela Universitaria de Magisterio, 2017)
The overall objective of this study is to prove whether some variables, such as autonomy support and positive affect experienced in the classroom, are predictors of academic performance through self-efficacy and engagement in university students. The tested model confirms the expected results but notes that self-efficacy does not show a significant direct effect on performance. Therefore, a second model is tested. We include self-efficacy as a predictor of academic engagement, eliminating the direct effect of this variable on performance. The results show a greater adjustment in the second model. It is concluded that: (a) positive emotions and autonomy support predict academic performance, self-efficacy and academic engagement; (b) self-efficacy predicts higher levels of academic engagement and the latter improves academic performance, and (c) indirect effects also show the existence of a mediation of these variables on the predictive relationship of autonomy support and positive emotions on performance. © 2017 Universidad del País Vasco. Published by Elsevier España, S.L.U.